49. THE RESULT OF INVASIVE MECHANICAL VENTILATION TREATMENT IN NEONATAL AND RELEVANT FACTORS WITH DISEASES MATERNAL IN BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the results of mechanical ventilation in newborns treated at the Department of Pediatrics, Bach Mai Hospital, and to identify some related factors from maternal pathology.Research methods: Using a cross-sectional descriptive method, studying 51 newborns treated with invasive mechanical ventilation at the Department of Pediatrics, Bach Mai Hospital from June 2019 to April 2020.Results: Newborns requiring invasive mechanical ventilation accounted for 15.1% of the total number of newborns with respiratory failure, in which the male/female ratio was 2/1. Infants in the group with mothers having pathologies (68.6%) were significantly higher than those in the group with mothers having no pathologies (31.4%) with p < 0.05. The rates of extremely premature, very premature, premature and full-term infants requiring mechanical ventilation were 15.7%; 47.1%; 29.4% and 7.8%, respectively. The average weight of infants in the group with mothers having pathologies (1510 ± 710g) was lower than that of infants in the group with mothers having no pathologies (1880 ± 1040g). The average duration of invasive mechanical ventilation of infants in the group with mothers having pathologies (8.5 ± 7.6 days) was higher than that of infants in the group with mothers having no pathologies (4.06 ± 3.3 days). Children born to mothers without the disease had a higher rate of successful treatment (93.8%) than children born to mothers with the disease (88.6%). The treatment failure rate (death) was 9.8%.Conclusions: Children born to mothers with disease had a higher mean duration of invasive mechanical ventilation and a lower success rate than children born to mothers without disease.
Keywords: Newborn; neonatal respiratory failure; invasive mechanical ventilation